Post - transcriptional regulation of seed dormancy and germination : current understanding and future directions - Tognacca, Rocío Soledad (2021)
Fil: Tognacca, Rocío Soledad. Universidad de Buenos Aires. Instituto de Fisiología, Biología Molecular y Neurociencias (IFIBYNE, CONICET-UBA). Buenos Aires, Argentina.